CORRELATION RELATIONSHIPS AGES, OFFICE BLOOD PRESSURE, EGFR, RENIN, ALDOSTERONE, METANEPHRYLS LEVELS IN PATIENTS WITH RESISTANT HYPERTENSION. (June 2018) - Rekovets, O.; Torbas, O.; Kushnir, S.; Primak, G.; Granich, V.; Ponomareva, G.; Sirenko, Y.
Abstract : Objective: The purpose of this analysis was to determine factors that contribute to poor blood pressure lowering in patients with resistant hypertension. Design and method: We examined and treated 1146 patients with AH and take 3 or more antihypertensive drugs (62.7% - women, 37.3% - men). Mean age was 57, 9 ± 0, 4 years, weight – 87, 7 ± 0, 6 kg/m2. At baseline mean office blood pressure (BP) was 174, 6/100, 5 ± 0, 6/0, 4 mmHg. Results: Mean office BP after treatment was 131, 3/80, 1 ± 0, 4/0, 6 mmHg. Patients had dyslipidemia - 65%, type 2 diabetes - 16.6%, cerebrovascular disease - 15.8% (ischemic stroke - 12.8%), thyroid disease - in 10.4%, including hypothyroidism - 2.8%, chronic pyelonephritis - 16.3%, obstructive sleep apnea - 3.3%, chronic kidney disease - 3.3%. Ages was correlation with weight (r = −0, 255, p < 0, 01), triiodothyronine (r = −0, 40, p < 0, 01), thyroid-stimulating hormone (r = 0, 169, p = 0, 01), eGFR (r = −0, 551, p < 0, 01), SBP after treatment (r = −0, 081, p < 0, 012), DBP after treatment (r = −0, 230, p < 0, 01), glucose (r = 0, 125, p < 0, 01), left ventricular myocardial mass index (r = 0, 159, p < 0, 01), potassium (r = 0, 077, p = 0, 01), takes beta-blockers (r = 0, 128, p < 0, 01), takes calcium antagonists (r = −0, 126, p < 0, 01). BMI was correlation with aldosterone levels (r = −0, 190, p = 0, 04), urine metanephryls (r = −0, 247, p = 0, 02). Renin level was correlated with total cholesterol (r = −0, 319, p = 0, 002), TG (r = −0, 267, p = 0, 02), office SBP after treatment (r = −0, 243, p = 0, 03), office DBP after treatment (r = −0, 230, p = 0, 04). SBP after treatment was correlated with men (r = 0, 135, p = 0, 001), eGFR (r = −0, 132, p = 0, 01), high density lipoproteins (r = −0, 170, p = 0, 007). DBP after treatment was correlated with potassium (r = −0, 066, p = 0, 041). Conclusions: Patients whose taken 3 or more antihypertensive drugs drugs less decreased BP was associated with male sex, less of renin level, less eGFR, bigger body mass index, was younger, less level of high density lipoproteins, less of potassium level, higher left ventricular myocardial mass index.